2022
DOI: 10.1007/s00586-021-07086-7
|View full text |Cite
|
Sign up to set email alerts
|

Variations in LOS and its main determinants overtime at an academic spinal care center from 2006–2019

Abstract: Objectives Efforts to safely reduce hospital LOS while maintaining quality outcomes and patient satisfaction are paramount. The primary goal of this study was to assess trends in LOS at a high-volume quaternary care spine center. Secondary goals were to assess trends in factors most associated with prolonged LOS. Methods This is a prospective study of all consecutive patients admitted from January 2006 to December 2019. Data included demographics, diagnostic category (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Patient consent was not required by our institutional ethics board as all patients have anonymized data collected prospectively in our study registry. Our study is a follow-up of our previously published work using the same patient population and dataset [ 16 ], however further analyzing factors impacting LOS that were previously not investigated to better understand why certain trends were observed in LOS over time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient consent was not required by our institutional ethics board as all patients have anonymized data collected prospectively in our study registry. Our study is a follow-up of our previously published work using the same patient population and dataset [ 16 ], however further analyzing factors impacting LOS that were previously not investigated to better understand why certain trends were observed in LOS over time.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously examined the trends of LOS over time at our institution [ 16 ], finding that the overall median LOS has not significantly changed over time between 2006 and 2019, while mean age has increased during this time. Additionally, in patients with degenerative pathology in particular, median LOS did increase over this period as well as the proportion of emergency admissions in this diagnostic group [ 16 ]. These results led us to thoroughly examine the specific factors that affected LOS among the same patient population as a follow-up study of our previously published work.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the aging population has led to additional spinal surgeries, with a high correlation between increasing age and more adverse events. 41 Concurrently, infection prevention protocols and technological advances have contributed to a reduction in adverse events, such as surgical site infections, resulting in a reduction in hospital length of stay (LOS) and associated costs. 1,41 Conversely, technological advances in implants as well as surgical navigation systems with intra-operative 3D imaging have likely increased the cost of care.…”
Section: Limitationsmentioning
confidence: 99%
“…41 Concurrently, infection prevention protocols and technological advances have contributed to a reduction in adverse events, such as surgical site infections, resulting in a reduction in hospital length of stay (LOS) and associated costs. 1,41 Conversely, technological advances in implants as well as surgical navigation systems with intra-operative 3D imaging have likely increased the cost of care. Based on a prospective study of patients who underwent spinal surgery from 2006 to 2019, Charlotte et al concluded that, in aggregate, these various factors that influence LOS (and associated costs) appear to have had the net effect of balancing each other out, further supporting the use of these previously published health insurance claims data analyses to inform costs.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation